Improving access to timely and quality sweetpotato vines in Tanzania - International Potato Center (2013)
Six months after the end of the project Decentralised Vine Multipliers (DVMs) continue e!orts to respond to the need for quality vines in their communities and see opportunities for additional income from vine and root sales.